REACTION OF WORKERS OF ODESA AND MYKOLAIV TO THE IMPLEMENTATION OF COMPLETE COLLECTIVATION AND ITS CONSEQUENCES (Південний архів (історичні науки), 2025)
This study analyzes, using archival sources, the situation of workers in Odesa and Mykolaiv during the first half of 1930. Specifically, it examines their reactions to the implementation of complete collectivization in rural areas and the resulting consequences – primarily, the severe deterioration of food supplies for urban workers. Using general scientific methods such as analysis, synthesis, and the historical method, the study identifies key aspects of workers' responses to collectivization and its effects. Findings: The research highlights how workers in Odesa and Mykolaiv reacted to collectivization and to peasant protests against government policies. It establishes that collectivization led to a sharp decline in food availability for workers. Additionally, it explores the various ways workers responded to these “food difficulties”. Conclusions: A significant portion of workers actively opposed the government's agrarian policies, which sought to transform independent farmers into collective farmers. Many workers expressed strong disapproval of collectivization and dispossession, recognizing that these measures would lead to agricultural decline and widespread famine. Workers also responded to peasant protests against collectivization, not only supporting them but also expressing a willingness to join. However, the most intense worker dissatisfaction arose from the worsening food shortages, which authorities downplayed as “food difficulties”. By March 1930, workers were receiving increasingly inadequate food rations, often of poor quality through the Central Workers' Cooperative system. This led to widespread frustration and culminated in open demonstrations, known as “bagpipes”, against the authorities.
Keywords: Central Workers' Cooperative, “food shortages”, peasant uprisings, State Political Administration